Malignant Transformation of a Neurofibroma - C. Alabado, Jibin; Valera, Eric; Regina Paula Valencia, Ma.; Yatco-Omaña, Elaine (Journal of Ophthalmic Science, 2021)
Malignant transformation of peripheral nerve sheath tumor (MPNST) may develop from a plexiform type of Neurofibromatosis 1 (NF1) or previously irradiated areas. Generally, MPNSTs occur in about 2% to 5% of neurofibromatosis patients. In this paper, we present a 58-year-old male patient with neurofibromatosis who developed MPNST of the eyelids and nasal area. The patient had a history of multiple excision biopsies for facial tumors in 22 years at different institutions, allegedly revealing neurofibromas on histopathological evaluation. A recent consult with the Otorhinolaryngology Service (ORL) prompted an excision biopsy with results consistent with neurofibroma. The mass recurred and enlarged even more rapidly compared to the previously excised tumor. The patient also developed four tumors on the eyelids hence the referral to Ophthalmology Service. The eyelid masses and nasal mass were excised by the Ophthalmology and ORL Services. Histopathology revealed identical MPNST characteristics on all excised tumors. The patient was eventually referred to the Oncology Service to evaluate radio and chemotherapy. A rapid change in the size of a preexisting neurofibroma, infiltration of the adjacent structures, intralesional hemorrhage, and pain usually indicates a possible malignant transformation into MPNST. A high index of suspicion is helpful for clinicians when presented with a case of a recurrent neurofibromatosis, even if the only sign is the rapid growth of the mass since management of MPNST is very different from neurofibromatosis.
Keywords: Neurofibroma; Malignant Peripheral Nerve Sheath Tumor; Neurofibrosarcoma